2007
DOI: 10.1074/jbc.m704645200
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and Synergistic Modification of Human RPA Stimulates Chromosomal DNA Repair

Abstract: The activity of human replication protein A (RPA) in DNA replication and repair is regulated by phosphorylation of the middle RPA2 subunit. It has previously been shown that up to nine different N-terminal residues are modified in vivo and in response to genotoxic stress. Using a novel antibody against phospho-Ser 29 , a moiety formed by cyclin-Cdk, we observed that RPA2 was phosphorylated during mitosis in nonstressed cells. Robust phosphorylation of Ser 29 was also seen in interphase cells following treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
211
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(241 citation statements)
references
References 50 publications
26
211
1
1
Order By: Relevance
“…Second, RPA2 phosphorylation in interphase cells stimulates repair of chromosomal DNA damage caused either by camptothecin or bleomycin treatment. 4 Because RPA phosphorylation does not significantly alter the high affinity of RPA for ssDNA, 7,8 a likely scenario is that phosphorylated RPA located at DNA damage sites recruits factors for DNA repair ( Fig. 2A).…”
Section: Rpa Activity In Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…Second, RPA2 phosphorylation in interphase cells stimulates repair of chromosomal DNA damage caused either by camptothecin or bleomycin treatment. 4 Because RPA phosphorylation does not significantly alter the high affinity of RPA for ssDNA, 7,8 a likely scenario is that phosphorylated RPA located at DNA damage sites recruits factors for DNA repair ( Fig. 2A).…”
Section: Rpa Activity In Mitosismentioning
confidence: 99%
“…Phosphorylation of the RPA2 subunit proceeds through a favored pathway in interphase cells. 4 Under DNA damage conditions that cause the generation of ssDNA, the resulting persistent RPA-ssDNA entities act to recruit and activate the ATR checkpoint kinase. Co-incident phosphorylation of Ser33 In interphase cells, formation of DSBs causes initial modification of S33 by ATR, stimulating phosphorylation of adjacent S23 and S29 by cyclin/Cdk2.…”
Section: Rpa Activity In Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that RPA2 has a distinctive pattern of phosphorylation in many tumour cell lines in response to replication and CHK1 inhibitors (Anantha et al, 2007;Liu et al, 2012). There is general agreement that Ser33 is a phosphorylation target for activated ATR (Anantha et al, 2007;Vassin et al, 2009). In contrast, Ser4/8 is mainly phosphorylated through ATM or DNAPK activity (Liu et al, 2012).…”
Section: Figure3 7 Decreased Chk1 Transcription In Htert-mentioning
confidence: 99%
“…In contrast, Ser4/8 is mainly phosphorylated through ATM or DNAPK activity (Liu et al, 2012). Ser4/8 phosphorylation of RPA is usually found only in the most hyper-phosphorylated forms of RPA2 during DNA replication stress following phosphorylation of Ser33 which is phosphorylated by ATR (Anantha et al, 2007).…”
Section: Figure3 7 Decreased Chk1 Transcription In Htert-mentioning
confidence: 99%